Surface currents in the Mid-Atlantic Bight: the role of the Gulf Stream versus wind - Tal Ezer (Frontiers in Marine Science, 2025)
Surface currents of the Mid-Atlantic Bight (MAB) were studied using high-frequency radar (HFR) observations at 6 km resolution during a 5-year period (2020–2024). The study’s focus on the role of the Gulf Stream (GS) contrasts with most past studies that focused on the seasonal wind-driven currents. Empirical orthogonal function (EOF) analyses of the daily HFR currents were conducted with and without the GS, revealing modes of current variability linked to the seasonal wind pattern and storms versus modes linked to GS variability. The remote impact of the GS on coastal currents is complex, with different impacts seen on different parts of the MAB. For example, unusual GS meanders that move close to the coast impact flow variability near the shelf-break front, while other locations may be influenced by the strength of the GS and shift in the mean position of the GS. In general, it was found that monthly wind may be responsible for approximately 50%–80% of the surface current variability over the entire MAB, while the GS position and speed are correlated with the offshore component of the coastal currents and linked to approximately 10%–30% of the current variability. There are also large interannual variations, so that during some years, the GS impact on the coast is larger than during other years. Comparison between geostrophic velocity derived from altimeter data and the HFR surface currents shows the influence of the GS path on the offshore currents; however, close to the coast, the currents are wind- and river-driven, so that geostrophic currents obtained from altimeter data are not reliable. Therefore, combining altimeter and HFR data will provide a better current field than each data set alone. The study demonstrates the usefulness of the HFR data to study coastal dynamics and links between the coast and open ocean variability.